Palmitoyl-carnitine production by blood cells associates with the concentration of circulating acyl-carnitines in healthy overweight women. Issue 5 (October 2017) - Chondronikola, Maria; Asghar, Rabia; Zhang, Xiaojun; Dillon, Edgar L.; Durham, William J.; Wu, Zhanpin; Porter, Craig; Camacho-Hughes, Maria; Zhao, Yingxin; Brasier, Allan R.; Volpi, Elena; Sheffield-Moore, Melinda; et al.
Summary: Background: Circulating acyl-carnitines (acyl-CNTs) are associated with insulin resistance (IR) and type 2 diabetes (T2D) in both rodents and humans. However, the mechanisms whereby circulating acyl-CNTs are increased in these conditions and their role in whole-body metabolism remains unknown. The purpose of this study was to determine if, in humans, blood cells contribute in production of circulating acyl-CNTs and associate with whole-body fat metabolism. Methods and results: Eight non-diabetic healthy women (age: 47 ± 19 y; BMI: 26 ± 1 kg·m −2 ) underwent stable isotope tracer infusion and hyperinsulinemic-euglycemic clamp study to determine in vivo whole-body fatty acid flux and insulin sensitivity. Blood samples collected at baseline (0 min) and after 3 h of clamp were used to determine the synthesis rate of palmitoyl-carnitine (palmitoyl-CNT) in vitro . The fractional synthesis rate of palmitoyl-CNT was significantly higher during hyperinsulinemia (0.788 ± 0.084 vs . 0.318 ± 0.012%·hr −1, p = 0.001); however, the absolute synthesis rate (ASR) did not differ between the periods ( p = 0.809) due to ∼30% decrease in blood palmitoyl-CNT concentration ( p = 0.189) during hyperinsulinemia. The ASR of palmitoyl-CNT significantly correlated with the concentration of acyl-CNTs in basal ( r = 0.992, p < 0.001) and insulin ( r = 0.919, p = 0.001) periods; and the basal ASR significantly correlated with plasma palmitate oxidation ( r = 0.764, p = 0.027). Conclusion: In women, blood cells contribute to plasma acyl-CNT levels and the acyl-CNT production is linked to plasma palmitate oxidation, a marker of whole-body fat metabolism. Future studies are needed to confirm the role of blood cells in acyl-CNT and lipid metabolism under different physiological (i.e., in response to meal) and pathological (i.e., hyperlipidemia, IR and T2D) conditions.